1998
DOI: 10.1159/000057361
|View full text |Cite
|
Sign up to set email alerts
|

Role of TGF-β in Vascular Development and Vascular Reactivity

Abstract: Transforming growth factor-β (TGF-β) is the prototypic member of a large family of structurally related proteins. Three vertebrate TGF-β isoforms have been identified and termed TGF-β1, TGF-β2, and TGF-β3, respectively. In addition, two receptors of the serine/threonine kinase family termed type I and II have also been identified. In this review, we focused our attention on the effects of TGF-β on vascular development and vascular reactivity. The critical role of the TGF-β1 and the TGF-β type II receptor in bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 46 publications
(72 reference statements)
0
17
0
1
Order By: Relevance
“…Therefore, induction of Igfbp2 and Prss11 during heterologous growth control may decrease vascularization of tumor cells in vivo. Suppression of tumor vascularization during heterologous growth control is also inferred by activation of the gene encoding endothelin, which can inhibit angiogenesis (44), in concert with suppression of genes encoding proliferin, which increase angiogenesis (45).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, induction of Igfbp2 and Prss11 during heterologous growth control may decrease vascularization of tumor cells in vivo. Suppression of tumor vascularization during heterologous growth control is also inferred by activation of the gene encoding endothelin, which can inhibit angiogenesis (44), in concert with suppression of genes encoding proliferin, which increase angiogenesis (45).…”
Section: Discussionmentioning
confidence: 99%
“…encoding BMP4 (Bmp4) and endothelin (Edn1) were increased over 2-fold. Interestingly, in addition to BMP4 signaling, induction of endothelin may decrease tumor vascularization (44).…”
Section: Mechanisms Of Heterologous Growth Controlmentioning
confidence: 99%
“…TGF-β signaling plays pivotal roles in SMC differentiation during vascular development as well as phenotypic switching in disease states [52] . The importance of TGF-β signaling pathway in SMC differentiation during embryonic development has been demonstrated by numerous studies [53] . Gene-targeting studies in mice have shown that a loss of TGF-β signaling components generally leads to abnormal differentiation and maturation of the primitive vascular network, resulting in defective vessels losing integrity of the vessel wall.…”
Section: Differentiation During Embryonic Developmentmentioning
confidence: 99%
“…TGFb signaling is thought to play a critical role in vascular development and function due to effects on endothelial cell proliferation and migration, fibronectin synthesis and mural cell differentiation (reviewed in Bohnsack and Hirschi, 2004;Perrella et al, 1998). This idea is supported by the fact that embryonic lethality in some Tgfb1 À/À mouse embryos is due to failed yolk sac vasculogenesis (Dickson et al, 1995).…”
Section: Introductionmentioning
confidence: 99%